PENGARUH HARGA, TRUST IN BRAND TERHADAP KEPUTUSAN PEMBELIAN DAN LOYALITAS KONSUMEN MINYAK GORENG MEREK BIMOLI DI KOTA PEKANBARU - Efiana Efiana; Jushermi Jushermi; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The study was to examinet the effect of price, Trust in Brand on Purchasing Decisions and Custumer Loyalty of Bimoli Brand Cooking Oil in Pekanbarru City. Primary data was collected by questionnaires to 120 custumers as a sample. Secondary data comes from the literature related to this study. The test hypotesis in this research is Path Analysiis with SPSS version 23. The result showed that 1) Price has a negative and significant on Purchase Decision of Bimoli brand cooking oil in Pekanbaru City 2)Trust In Brand has a positive and significant on Purchase Decision of Bimoli brand cooking oil in Pekanbaru City 3)Purcahase Decision has a positive and significant on Custumer Loyalty of Bimoli brand cooking oil in Pekanbaru city 4)Price has a negative and significant efeect on Custumer Loyalty through Purchasing Decision of Bimoli brand cooking oil in Pekanbaru City 5) Trusi in Brand positive and significant efeect on Custumer Loyalty trough Purchasing Decision of Bimoli brand cooking oil in Pekanbaru City.Keywods: Price, Trust in Brand, Purchasing Decision, Custumer Loyalty.